Glucose Metabolism, Thyroid Function, and Prolactin Level in Adolescent Patients With First Episode of Schizophrenia and Affective Disorders - Petruzzelli, Maria Giuseppina; Marzulli, Lucia; Giannico, Orazio Valerio; Furente, Flora; Margari, Mariella; Matera, Emilia; Margari, Francesco (Frontiers in Psychiatry, 2020)
Schizophrenia and affective spectrum disorders typically begin in adolescence or early adulthood. The pathophysiological mechanisms underlying these disorders are still not fully understood, and recent studies have suggested an involvement of multiple systems at the onset of these disorders including dysfunctions in cardiometabolic, immune-inflammatory and neuroendocrinological systems. In this context, we aimed to assess thyroid function, prolactin level, glucose metabolism and lipid profile in drug naive adolescents, comparing patients with first episode of schizophrenia spectrum disorders (SSD) and patients with affective spectrum disorders (ASD). We performed a retrospective chart review from inpatients aged from ten to eighteen years, referred to Child and Adolescent Psychiatric Unit of University of Bari “Aldo Moro” over a period of four years, with diagnosis of SSD (n=30) or ASD (n=22), according to DSM-5 criteria. Data on serum prolactin, glucose, insulin, total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol, triglycerides, thyroid stimulating hormone, free triiodothyronin, and free thyroxin were collected, and the insulin resistance index “HOMA-IR” was calculated. The multivariable linear regression models, adjusting for potential confounding factors (age, sex and BMI), showed HOMA-IR (p=0.001), glucose (p=0.004), insulin (p=0.004) and free thyroxin (p<0.001) values higher in the SSD group than in ASD. No others significant differences were found. Our findings suggest the need for a metabolic and endocrine screening at the onset of SSD and ASD, particularly for indexes of insulin resistance, that is a testable and treatable risk factor for cardiometabolic diseases. Further studies are needed to better understand the role of endocrinological and metabolic dysfunctions at the onset of severe mental illness also considering influencing factors as age, gender and BMI.